Study of Empowerment and Satisfaction to Boost Performance of Worker - Kartika, Dita Cucu; Rugaiyah, Rugaiyah; Akbar, Ma’ruf (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
The objective of this research is to understand the effect of empowerment and job satisfaction toward job performance of lecturer in Majalengka University, West Java comprehensively. A survey method with path analysis techniques was used by applying a questioner as a research instrument. 80 responders were involved by sending their feedback within the questioner. Those responders were decided using simple random sampling among all lecturers that working at the Majalengka University. The data result, analysis, and interpretation reveal that (1) empowerment has a direct positive effect on job performance, (2) job satisfaction has an immediate positive impact on job performance, (3) empowerment has a direct positive impact on job satisfaction.